EFEKTIVITAS PEMBELAJARAN DARING DI MASA COVID-19 TERHADAP HASIL BELAJAR SISWA SMK N 20 JAKARTA - Adinda Lutfiana; Indriani Sri Lestari; Khairu Annisa; Sarah, Sarah; Nida Handayani (Badan Penerbit STIEPARI Press, 2022)
Online learning serves as a liaison between teachers and students with an internet network that can be accessed anytime and anywhere. The online media used by the research subjects are various (WhatsApp, Zoom Meeting, google classroom, and Website). Various problems are experienced by students with this online learning system, such as signal problems, internet fees, and instant learning systems. The purpose of this study was to analyze the effectiveness of online learning applied at the 20 South Jakarta state vocational high school levels. The method used in this study is the method of observation and interviews conducted with the children of SMK N 20 South Jakarta. The results showed that online learning was considered less effective in quality student learning outcomes. Because online learning limits the interaction space between teachers and students and students with other students. So there is a lack of interaction to discuss learning materials.